SISTEM APLIKASI PEMESANAN BIBIT IKAN BERBASIS WEB (PROGRAMMING) Studi Kasus (Kabupaten Kampar) - Andes Vilma; Emon Azriadi; Deddy Gusman (Universitas Pahlawan Tuanku Tambusai, 2022)
The online marketplace can make it easier for fish breeding businesses to promote products and make it easier for consumers to get information about the products owned by the breeder. Limitations of product marketing are an obstacle for a fish breeder in increasing sales, moreover, manual reporting harms fish breeder by recording sales reports, so that sales and inventory reports are obstructed.The purpose of this research is to create an e-commerce-based online sales website that can be accessed online. The method used by the researcher in this research is the waterfall method. This method is used by researchers to build a software sistem by having a software flow starting with sistems engineering, analysis, design, coding, testing, and maintenance. The sistem design uses Unified Modeling Language, PHP programming language, and MySQL database.This research is conducted on a web-based online sales application that provides real-time inventory information, sales reports, inventory reports, fish seed production annual report and sellers can promote the products they sell by fish farmers in kampar district. Because of the process of reporting and checking inventory, the information can be carried out correctly and the seller's marketing reach can be wider so that it can increase income for fish breeding farmers in Riau Province especially in the district of kampar. Keywords: fish breeder, e-commerce, website, php, mysql